Marketing elements and operator characteristics on the success of the business operation of the elderly in Thailand - Paengkesorn , Rujapa (Business Administration and Economics Review, 2021)
This research aims to study the marketing’s components and characteristics of entrepreneurs toward the success of senior product entrepreneurs’ business operation in Thailand. The sample group in this research was 400 entrepreneurs of elderly products in various groups by using questionnaires. The statistics were used in questionnaire analysis: mean, percentage, standard deviation and hypothesis analysis. The research results found that most of the respondents were female, aged between 30 to 39 years old with a bachelor’s degree. The period of business operation was usually 5 to 10 years with less than 20 employees and operated with single-owner type of business. Additionally, an average monthly business income was less than 1 million baht. Marketing elements which affected the success of the elderly products’ business operation were summarized as follows. All of the marketing components were ranked at high level in every aspect. For the ‘Product,’ reliability of product’s quality with clearly identified sources was ranked at high level. Meanwhile, for the ‘Price,’ appropriateness of product’s price and quality was ranked at the highest level. Moreover, for the ‘Distribution Channels,’ information provided by employees through distribution channels was ranked at high level. Lastly, for the ‘Promotion,’ staffs with plenty of product’s knowledge was ranked at high level. Entrepreneurs’ traits on the success of senior product entrepreneurs’ business operation in Thailand can be summarized as follows. All of the entrepreneurs’ traits were ranked at high level in every aspect. For the ‘Creativity,’ finding opportunities among the business’ problems was ranked at high level. Moreover, for the ‘Innovation Creativity,’ having ideas to sell new products was ranked at high level while for the ‘Risk Acceptance,’ acknowledgement of business operation was also ranked at high level. For the ‘Management Capabilities,’ listening to all internal employees’ opinions was ranked at high level, along with a survey of customers’ and partners’ needs for ‘Business Determination’ was also ranked at high level. Factors of business operation’s success of senior product entrepreneurs in Thailand were summarized as follows. The selection of quality products and distribution of new products which are not close to an expiration date were ranked at the highest level by the participants for ‘Building quality products and services’ aspect. For ‘Employees’ Participation,’ approval of employees’ participation in developing the business was ranked at high level. In addition, for ‘Responding to customers’ needs,’ listening to customers’ opinions was ranked at high level. Meanwhile, for ‘Creativity and Innovation,’ setting a clear target to increase sales volume was ranked at high level, while reduction in business expenditures in the previous year was also ranked at high level for the aspect of ‘Financial success.’